165Ethnic differences in type 2 diabetes mortality and hospitalisation rates in a New Zealand population1994-2018. (2nd September 2021) - Yu, Dahai; Osuagwu, Levi; Pickering, Karen; Baker, John; Cutfield, Richard; Orr-Walke, Brandon; CaI, Yamei; Zhao, Zhanzheng; Simmons, David
Abstract: Background: Type 2 Diabetes (T2DM) affects different populations disproportionately including in New Zealand (NZ), where long-term temporal trends in cause-specific clinical outcomes between Māori, European and Pacific people remain unclear. Methods: Data from patients with T2DM, aged 35-84 years enrolled 1994-2018 in a NZ primary care audit programme (the Diabetes Care Support Service) were linked with national death registration, hospitalisation, pharmaceutical claims and primary care databases. Cause-specific death and hospitalisation rates were adjusted for gender, age, smoking, obesity, social-economic status and time periods by age-period-cohort models. Results: Overall, 79, 912 (50.6% female, mean-age 56±15 years, median follow-up 9.7 years) patients with T2DM were enrolled. For Europeans vs Māori, adjusted incidence rates ratio (IRR) and absolute risk difference /1000 person-years were 1.96 (95% CI: 1.80- 2.14) and 22.85 (19.93-25.77) for all-cause mortality, 1.93 (1.63-2.29) and 6.97 (5.14-8.80) for cardiovascular (CVD) mortality, 1.64 (1.40-1.93) and 3.08 (2.25-3.92) for cancer mortality, 1.26 (1.25-1.28) and 42.70 (41.32-44.08) for CVD hospitalisation, 1.31 (1.28-1.34) and 44.76 (42.37-47.15) for cancer hospitalisation, 2.05 (1.96-2.14) and 31.44 (29.67-33.21) for end-stage renal disease (ESRD) hospitalisation. Pacific rates were significantly less than Māori, but higher than Europeans for ESRD (IRR:1.59 (1.52-1.67)) and CVD (1.09 (1.07-1.10)) hospitalisation. Conclusions: Poorer health outcomes have persisted among Māori and Pacific people with T2DM for >20 years. New policies supporting more intensive management of T2DM are urgently needed. Differences in outcomes between Māori and Pacific people warrant further research. Key messages: Outcome disparities have persisted among Māori and Pacific people with T2DM for >20 years.